2021
DOI: 10.1029/2021jb022188
|View full text |Cite
|
Sign up to set email alerts
|

Repeating Nontectonic Seasonal Stress Changes and a Possible Triggering Mechanism of the 2019 Ridgecrest Earthquake Sequence in California

Abstract: Dense spatial and temporal coverage of continuous global positioning system (cGPS) measurement enables rigorous investigations of time-dependent surface strain anomaly patterns in California. Observed by cGPS, the seasonality in the crustal nontectonic strain and the associated stress changes are attributable to the Earth's elastic response (Farrell, 1972) to time-varying loading sources on the surface, such as hydrologic loads (e.g., Argus et al., 2014), atmospheric pressure (e.g., Gao et al., 2000, and therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…This correlation also holds for damaging M>5.5 earthquakes in catalogs reaching back to 1781 (Johnson et al, 2017a). Horizontal GNSS displacements have also been used to estimate seasonal strain variations and to discuss their potential association with seismicity in California (e.g., Kreemer and Zaliapin, 2018;Kim et al, 2021b). Kreemer and Zaliapin (2018) proposed that hydrologically induced seasonal strain may cause a larger stress release in an earthquake and fewer aftershocks.…”
Section: Seasonal Hydrological and Atmospheric Loadsmentioning
confidence: 99%
See 1 more Smart Citation
“…This correlation also holds for damaging M>5.5 earthquakes in catalogs reaching back to 1781 (Johnson et al, 2017a). Horizontal GNSS displacements have also been used to estimate seasonal strain variations and to discuss their potential association with seismicity in California (e.g., Kreemer and Zaliapin, 2018;Kim et al, 2021b). Kreemer and Zaliapin (2018) proposed that hydrologically induced seasonal strain may cause a larger stress release in an earthquake and fewer aftershocks.…”
Section: Seasonal Hydrological and Atmospheric Loadsmentioning
confidence: 99%
“…GNSS time series to calculate the strain and stress changes in the northern San Francisco Bay Area and found the 2014 M6.0 South Napa earthquake occurred during a period with peak seasonal Coulomb stress. Using a similar method, Kim et al (2021a) reported that the 2019 Ridgecrest earthquake sequence took place at a time with higher seasonal stress. Both studies suggested the possible earthquake triggering from non-tectonic seasonal loading in California (Johnson et al, 2017a).…”
Section: Deformation and Seismicity From Changing Climate And Weathermentioning
confidence: 99%
“…Note that the observed stress rotations may not imply temporal variations of the stress field but may reflect noise due to inherent uncertainties in the focal mechanisms and stress inversions (Hardebeck, 2012;Townend and Zoback, 2001;Townend et al, 2012), and/or local stress heterogeneities prior to the mainshock (Smith and Dieterich, 2010;Yukutake et al, 2007Yukutake et al, , 2010 which contradict the assumed uniform stress field in the chosen spatial bin. Local stress heterogeneities are likely to be common and can be caused by geometrical changes of faults, heterogeneous non-tectonic local loadings and other mechanisms (Ben-Zion, 2008;Kim et al, 2021).…”
Section: Local P-axis Rotation After Major Rupturesmentioning
confidence: 99%
“…Observations suggest that the seismicity rate can be influenced by both static and dynamic perturbations. Solid [320][321][322], liquid [323] and polar tides [324], seasonal stress patterns [325][326][327][328], and anthropogenic actions such as fluidinjection [329][330][331] can affect seismicity. The case of tides is really interesting because of the tiny size of tidal shear stress σ s ∼ 0.1−1 kPa with respect to the typical stress drop during earthquakes σ ∼ 1-10 MPa.…”
Section: The Effect Of Terrestrial Gradients On the Features Of Earth...mentioning
confidence: 99%